PI3K/Akt/mTOR signaling pathway and malignant hepatobiliary tumors - CHEN Xuxiao (Linchuang Gandanbing Zazhi, 2015)
Phosphoinositide-3 kinase/protein kinase-B/mammalian target of rapamycin (PI3K/Akt/mTOR) signaling pathway is involved in many important biological processes such as cell metabolism, growth, proliferation, and angiogenesis. And its high-level activation is closely related to the development and progression of many malignant tumors. In this paper, mTOR and PI3K/Akt/mTOR signaling pathway are introduced, and their action mechanisms in the development and progression of hepatocellular carcinoma, cholangiocellular carcinoma, cholangiocarcinoma, and gallbladder carcinoma are expounded, and then the role of mTOR inhibitors in the treatment of malignant hepatobiliary tumors is briefly described. It is thought that the PI3K/Akt/mTOR signaling pathway provides new therapeutic targets for malignant hepatobiliary tumors in advanced stage and the constant development of new mTOR inhibitors provides some new hope for the patients with malignant hepatobiliary tumors in advanced stage.